1998
DOI: 10.1038/sj.bjp.0702259
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous angiotensin II and the reflex response to stimulation of cardiopulmonary serotonin 5HT3 receptors

Abstract: 1 Angiotensin (Ang) II modulates cardiovascular barore¯exes; whether or not the peptide in¯uences chemosensitive cardiovascular re¯exes is not known. We tested the hypothesis that Ang II modulates the re¯ex control of sympathetic nerve activity exerted by 5-hydroxytryptamine 3 (5HT 3 ) cardiopulmonary receptors. 2 The 5HT 3 receptor agonist phenylbiguanide (PBG), infused intravenously for 15 min, elicited a sustained re¯ex decrease of renal sympathetic nerve activity (RSNA) but only transient (53 min) changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…Veelken et al (42) reported that acutely administered ANG II blunted, but did not abolish, the renal sympathoinhibitory response to VE (42). Our data, however, do not confirm this finding.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Veelken et al (42) reported that acutely administered ANG II blunted, but did not abolish, the renal sympathoinhibitory response to VE (42). Our data, however, do not confirm this finding.…”
Section: Discussioncontrasting
confidence: 57%
“…This is surprising given that normal VE-induced inhibition of renal SNA is attenuated in animals with established congestive heart failure (CHF) (5,11,12), which is subsequently improved after AT 1 receptor blockade (12). These results indicate that ANG II may alter the cardiopulmonary-renal reflex (12,42), potentially contributing to the sympathoexcitation in disease states such as CHF in which extracellular fluid (ECF) volume becomes progressively increased in the presence of elevated circulating ANG II.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Indeed, the pro®le of cardiovascular eects of anandamide resembled, in several respects, those of 5-HT, which triggers the von Bezold-Jarisch re¯ex through stimulating 5-HT 3 -receptors on vagal aerent ®bres, with subsequent vagal eerent activation (Veelken et al, 1998). The only vascular bed to show vasodilatation in response to anandamide was the hindquarters, which is consistent with the eects of the synthetic cannabinoid, WIN 55212-2, in our model (Gardiner et al, 2001;2002a, b).…”
supporting
confidence: 64%